Constructing chaotic transformations with closed functional forms - Weihong Huang (Discrete Dynamics in Nature and Society)
The properties of complete chaotic unimodal transformations with closed functional forms are examined and the necessary and sufficient conditions are provided to construct such transformations. Theoretical findings are verified with computer simulations.